Distribution, biomass, and year-to-year dynamics of Sagitta in the Okhotsk Sea - Konstantin M. Gorbatenko (Известия ТИНРО, 2016)
Arrowworms, presented mostly by a complex species Sagitta elegans , form from 16.5 % (in summer) to 24.1 % (in winter) of zooplankton biomass in the Okhotsk Sea, with the mean annual value varied in the range 170.7-230.9 mg/m3 (the data of long-term surveys conducted by Pacific Fish, Res. Center, TINRO averaged for 1986-2012). Their abundance is the highest in winter-spring and the lowest in autumn. The main feature of their spatial distribution is the abundance increasing toward coasts, and the highest concentrations are usually found on the western shelf of Kamchatka, including the Shelikof Bay. However, in summer-autumn their dense concentrations (> 500 mg/m3) are observed sometimes in the deep-sea areas, too. Mean total stock of this taxon in the Okhotsk Sea is assessed as 52.0 · 106 t in spring, 43.1 · 106 t in summer, 38.2 · 106 t in autumn, and 46.6 · 106 t in winter. Recently (since 1997) the total stock in spring ranges between 11.2-38.5 million ton and has even higher variability in winter. The variations of winter-spring stock determine changes in Sagitta juveniles abundance in autumn. Daily food ration of Sagitta is 4.0-6.0 % of body weight for juveniles and 1.5-2.0 % for adults; their mean total annual consumption in the Okhotsk Sea is estimated as 320 million ton, mainly copepods (87.9 % or 281.4 · 106 t that is 64.7 % of Copepoda stock). The other mass prey, as euphausiids, are weakly used by Sagitta (6.1 · 106 t/year or 1.9 % of their total consumption and 2.2 % of Euphausia stock) because they consume mainly eggs and nauplii of euphausiids. Cannibalism of Sagitta is estimated as 2.0 % of their stock annually.